A label‐free ratiometric method to detect Hg2+ based on structural change of DNA. (2nd September 2021) - Xu, Mingming; Peng, Yu; Liu, Huan; Tian, Xinyu; Yang, Hualin; Zhou, Yu
Abstract: In this work, a simple ratiometric method has been designed to detect Hg 2+ based on the structural change between double‐stranded DNA (dsDNA) and its G‐quadruplex structure. When Hg 2+ was added, the designed G‐quadruplex structure could change into the corresponding dsDNA by forming the T–Hg 2+ –T mismatch. This kind of variation resulted in a decrease in the fluorescence of the G‐quadruplex/ N ‐methyl mesoporphyrin IX (NMM) complex and an increase in the fluorescence from the dsDNA/SYBR Green I (SG I) pair. The secondary excitation wavelength of SG I was used to excite NMM and SG I simultaneously. The titration experiment indicated that the new method had a linear response within 0.7–2.5 μM Hg 2+ with a limit of detection of 9.3 nM. Because using the T–Hg 2+ –T mismatch to recognize Hg 2+ was very specific, the selectivity of the new method was also satisfactory. The recoveries ranged from 92.8% to 110.2% suggested that this new method could achieve a potential application for Hg 2+ detection in real environmental samples. Abstract : A simple ratiometric method for Hg 2+ detection based on the structural change between the G‐quadruplex and dsDNA was developed. This kind of variation resulted in a decrease in the fluorescence from the G‐quadruplex/NMM complex and an increase in the fluorescence from the dsDNA/SG I pair.